A Challenging Case of an Ectopic Cushing Syndrome - Joana Menezes Nunes; Elika Pinho; Isabel Camões; João Maciel; Pedro Cabral Bastos; Conceição Souto de Moura; Paulo Bettencourt (Case Reports in Medicine)
Bronchopulmonary carcinoids are rare pulmonary neoplasms although they account for most cases of ectopic ACTH syndromes. When feasible, the mainstay treatment is surgical resection of the tumor. We report the case of a 52-year-old woman with signs and symptoms suggestive of hypercortisolism for 12 months, admitted to our department because of community acquired pneumonia. Blood hormone analysis showed increased levels of ACTH and urinary free cortisol and nonsuppressibility to high- and low-dose dexamethasone tests. Pituitary MRI showed no lesion and no central-to-peripheral ACTH gradient was present in bilateral inferior petrosal sinus sampling. CRH stimulation test suggested an ectopic ACTH source. Thoracic CT scan revealed a nodular region measuring 12 mm located in the inferior lingular lobule of the left superior lung with negative uptake by 18-FDG-PET scan and negative SRS. The patient was successfully treated with an atypical lung resection and histology revealed an atypical bronchial carcinoid tumor with positive ACTH immunoreactivity. This was an interesting case because the patient was admitted due to pneumonia that may have been associated with her untreated and chronic hypercortisolism and a challenging case of ectopic ACTH syndrome due to conflicting results on the diagnostic exams.